2013
DOI: 10.2214/ajr.12.10209
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Efficiency of Low-Dose CT Angiography Compared With Conventional Angiography in Peripheral Arterial Occlusions

Abstract: CTA of peripheral arteries with a low tube voltage of 70 kV provides reliable information and serves as a rapidly performed and easily available "one-stop-shop" imaging modality in the diagnosis of peripheral arterial occlusion diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 28 publications
1
30
1
1
Order By: Relevance
“…6,[16][17][18][19][20][21][22] High-pitch acquisition allows for imaging of the whole aorta in less than 2 seconds, 12 thus avoiding long exposure time and reducing radiation dose and required administered volume of contrast agent. The CTA with lower tube voltages at 100 kVp and 6,24,25 which demonstrated that such techniques maintain diagnostic image quality while allowing for lower radiation dose and contrast agent volume.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,[16][17][18][19][20][21][22] High-pitch acquisition allows for imaging of the whole aorta in less than 2 seconds, 12 thus avoiding long exposure time and reducing radiation dose and required administered volume of contrast agent. The CTA with lower tube voltages at 100 kVp and 6,24,25 which demonstrated that such techniques maintain diagnostic image quality while allowing for lower radiation dose and contrast agent volume.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies emphasized the potential of 70-kVp CTA for assessment of peripheral artery, coronary artery diseases and cerebral artery. [16][17][18][19][20][21][22][23] Qi et al 18 demonstrated that 70-kVp acquisition during lower extremity high-pitch CTA with IR allows for a significant reduction of radiation dose and contrast material volume without compromising image quality despite a slight increase in image noise. Zhang et al 19 found that prospectively ECG-triggered high-pitch coronary CTA at 70 kVp with 30 mL of contrast agent is able to provide diagnostic image quality at a radiation dose of less than 0.2 mSv in patients with a body mass index below 25 kg/m 2 and a heart rate of less than 70 beats per minute.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 However, it is interesting to note that higher sensitivities and specificities obtained under these conditions do not necessarily translate into clinical relevance. Different patients with the same degree of luminal narrowing in the same vascular segment might present with different clinical symptoms or might even be free of symptoms, partially due to various degrees of muscular remodeling and collateralization.…”
mentioning
confidence: 99%
“…However, the reported sensitivities and specificities are comparable to more recently published data for CE-MRA and CTA obtained with modern hardware and software modalities. 3,4 The performance of DUS in the infrapopliteal runoff via the crural (tibial/peroneal arteries) and pedal vessels compared to DSA was analyzed separately in five selected citations. 11,12,16,18,21 This was most recently studied by the Joint Endovascular and Non-Invasive Assessment of LImb perfusion (JENALI) Group, which used a novel anatomical scoring system to compare its ability to detect patent or occluded vessels compared to DSA.…”
mentioning
confidence: 99%